An Analysis of Subjectivation Processes Mediated by New Digital Technologies - Ramos, Douglas Rossi [UNESP] (Kassel Univ Press Gmbh, 2020)
The new advent of digital, recurrently called by some authors as Web 2.0, Web 3.0 and Internet of Things, less than a mere technological change, consists of a new communicational paradigm. Mobile technologies, such as smartphones, have gained increasing prominence as means and tools of communication and mediators of interaction, in such a context. In this work, we intend to discuss mobile technology, especially smartphones, as mediators of social practices and modes of subjectivity today. For the analysis, the notion of remediation by the Spanish sociologist Amparo Lasen was used, which, in a general scope, concerns the reconfiguration of mediations on the self-practices due to the adoption of new technologies as mediators of social practices. Among the results, the subjectivity process mediated by mobile technologies can be divided into two axes of analysis: One referring to identification, knowledge sharing and self-awareness, and the other to control and dependence. The use of this type of digital mobile technology, such as smartphones, does not consist merely of just 'one more' media technology, which would minimally influence the processes of constituting subjectivities, on the contrary, it relates to an effective device for intermediating self and social-practices.
Keywords: Digital; Mobiles; Remediation; Self-Practices; Smartphones